AUDIT SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER UNTUK FINANCIAL REPORT - Peniarsih, Peniarsih (Universitas Dirgantara Marsekal Suryadarma, 2019)
By processing transactions that already use computers, namely Computer-Based Accounting Information Systems. The accounting process carried out for processing transactions / data, enough users / users only by entering data / transactions, so that the data will automatically be integrated and can make up to date Financial Report information. To keep the system reliable and trustworthy, it is necessary to audit a computer-based accounting information system so that financial reports produce information that is relevant, timely, accurate, complete and summarized. Finannial report, up to date, relevant, audit.Â Keyword : Audit, Sistem Informasi. Akuntani, Financial Report